Idarucizumab for Reversal of Dabigatran - Sheikh‑Taha, Marwan (2019)
Background Idarucizumab is used to reverse the effects of dabigatran. Information on the use of idarucizumab in the clinical setting remains very limited. Objective The objective of this study was to describe clinical experience with idarucizumab in a large medical teaching center in the USA. Methods Patients who received idarucizumab to reverse the effects of dabigatran between 1 January 2016 and 30 June 2018 were studied. In patients with major bleeding, the efficacy of idarucizumab was assessed using criteria of the International Society of Thrombosis and Hemostasis Scientific and Standardization Subcommittee. The course of treatment and clinical outcomes in patients who received idarucizumab for emergency surgery or procedures are described. Results In total, 13 patients received idarucizumab for atrial fibrillation during the study period. Their mean age was 77.5 ± 7.1 years, and 12 (92.3%) were men. Idarucizumab was used in 11 patients for major bleeding events and in two patients for emergency surgery or procedures. Intracranial hemorrhage (n = 6) and gastrointestinal bleed (n = 2) were the most common types of bleeding. Clinical hemostasis was achieved in 8 of 11 (72.7%) patients with major bleeding. One patient with acute kidney injury needed two doses of the reversal agent to achieve hemostasis. One patient underwent open heart surgery and developed postoperative hemorrhage despite receiving idarucizumab. None of the patients experienced thrombotic complications or side effects that could be attributed to idarucizumab. Conclusion Real-world experience in a US hospital with the use of idarucizumab in emergency situations requiring the reversal of the effects of dabigatran is described. Idarucizumab represents an exciting new antidote for dabigatran, but clinical efficacy and cost-effectiveness data remain lacking.